Awareness, attendance, and attitudes toward cervical cancer screening among HIV-positive Chinese women in Yunnan province: a cross-sectional study - Jiawei Hu; Rufei Duan; Hongyun Zhang; Xuelian Zhao; Aihui Wu; Le Li; Fanghui Zhao; Yong Zhang (BMC Women's Health)
Abstract Background Cervical cancer is a major health threat in the female population. Human immunodeficiency virus (HIV)-positive women encounter a higher risk of cervical cancer. It is significant to promote cervical cancer screening attendance among HIV-positive women. Little is known about the awareness, attendance, and attitudes toward cervical cancer screening, as well as the associated factors, among Chinese HIV-positive women. Methods A cross-sectional study was conducted among 411 HIV-positive women attending a large ART clinic in Yunnan, an HIV-endemic province in China. Participants were recruited using the convenient sampling method from January 2019 to August 2020. An interviewer-administered semi-structured questionnaire was utilized to collect information on socio-demographic and behavioral characteristics, clinical characteristics related to HIV infection, awareness, attendance, and attitudes toward cervical cancer screening. Binary logistic regression analyses were used to determine factors associated with awareness, attendance, and attitude toward cervical cancer screening. Results Some 69.8% (287) of the participants were aware of cervical cancer screening, but only 27.7% (114) had attended screening within 3 years. After receiving a brief health education, 72.3% (297) of the participants exhibited a positive attitude toward cervical cancer screening. Participants with a higher education background and longer duration of antiretroviral therapy were more likely to be aware of cervical cancer screening and have up-to-date screening. The up-to-date screening attendance was also influenced by age, smoking status, and health insurance. Single participants were less likely to show a positive attitude toward cervical cancer screening compared married or cohabiting counterparts. The main facilitators to attending cervical cancer screening were health promotion activity and well-organized programs, while the main barriers were high costs of the service and inadequate awareness. Conclusions Although most HIV-positive women attending a large ART clinic in Yunnan were aware of cervical cancer screening, the up-to-date attendance was low. It is crucial to conduct health education and promotion through efficient channels to improve awareness and attendance. The discrepancy between awareness and attendance also emphasized the importance of adopting appropriate screening strategies and powerful health policies that can foster the attendance of cervical cancer screening among HIV-positive women. Efforts should be devoted to constructing a comprehensive healthcare system with high accessibility in China for cervical cancer prevention and management for HIV-positive women.